Principles and Practices of Teaching English as an International Language. - Matsuda, Aya (Channel View Publications, 2012)
This book critically examines current ELT practices visàvis the use of English as an international lingua franca. It bridges the gap between theoretical discussion and the practical concerns of teaching English as an international language, and presents diverse approaches for preparing competent users of English in international contexts.